2020
DOI: 10.1002/cbdv.202000276
|View full text |Cite
|
Sign up to set email alerts
|

Sequences of Tolypins, Insecticidal Efrapeptin‐Type Peptaibiotics from Species of the Fungal Genus Tolypocladium

Abstract: A peptide mixture named tolypin, originally isolated from species of the fungal genus Tolypocladium, was structurally characterised and sequences compared to those reported for efrapeptins isolated from strains of Tolypocladium inflatum. Chiral amino acid analysis, direct infusion, and online HPLC electrospray ionization tandem mass spectrometry provided composition, molecular weights of peptides, and series of diagnostic fragment ions. Sequences deduced from ESI‐MS revealed that tolypins C−G are identical to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Only cyclosporins L, P, and 27 contain the Bmt residue that we found in tolypocladamides A–E . The efrapeptins, another series of linear peptides with antifungal, insecticidal, ATPase inhibitory, and antitumor activities, have been reported from the genus Tolypocladium . ,, The characterization of a mixture of peptides named tolypins isolated from Tolypocladium species revealed that these tolypins are similar to those efrapeptins except for tolypin H1 . Elvapeptins, an added series of peptides similar to efrapeptins, have been identified from T. inflatum ; however, no sequence is reported .…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Only cyclosporins L, P, and 27 contain the Bmt residue that we found in tolypocladamides A–E . The efrapeptins, another series of linear peptides with antifungal, insecticidal, ATPase inhibitory, and antitumor activities, have been reported from the genus Tolypocladium . ,, The characterization of a mixture of peptides named tolypins isolated from Tolypocladium species revealed that these tolypins are similar to those efrapeptins except for tolypin H1 . Elvapeptins, an added series of peptides similar to efrapeptins, have been identified from T. inflatum ; however, no sequence is reported .…”
Section: Resultsmentioning
confidence: 77%
“…15,16,28 The characterization of a mixture of peptides named tolypins isolated from Tolypocladium species revealed that these tolypins are similar to those efrapeptins except for tolypin H1. 29 Elvapeptins, an added series of peptides similar to efrapeptins, have been identified from T. inflatum; however, no sequence is reported. 30 In summary, the genus Tolypocladium is a valuable source of biologically active peptides.…”
Section: Journal Ofmentioning
confidence: 99%
“…Pip (4-aminopiperidine-4-carboxylic acid) is a naturally occurring amino acid found on Efrapeptin peptides, which are produced by fungi of the species Tolypocladium [ 161 ]. This class of peptides has antifungal, insecticidal, and mitochondrial ATPase inhibitory activities [ 161 , 162 ]. The right-handed α-helical structure cannot be adopted by Pip-rich peptides.…”
Section: Peptidomimetics Designmentioning
confidence: 99%
“…These molecules constitute a highly varied mixture of antibiotic peptides generated by some fungi, such as Tolypocladium niveun, Beauveria nivea, and Tolypocladium Perspective Chapter: Secondary Metabolites of Entomopathogens as Biotechnological Tools... DOI: http://dx.doi.org/10.5772/intechopen.111465 cylindrosporum [21]. A nonpolar extract from a culture broth of Beauveria bassiana showed toxic activity against the red potato beetle.…”
Section: Efrapeptinsmentioning
confidence: 99%